Study on the controller factors associated with roof falling and ribs spalling in deep mine with great mining height and compound roof. (November 2021) - Wang, Jiaqi; Zhang, Qiang; Zhang, Jixiong; Liu, Hengfeng; Zhu, Gaolei; Wang, Yunbo
Highlights: A critical rib spalling equation was developed based on compound beam model. Cohesion of coal is the major factor in controlling the stability of coal wall. A method for preventing roof fall and rib spalling was proposed. Abstract: To analyze the controllable factors associated with roof fall and rib spalling during the mining process in a deep well with a great mining height and compound roof, and to resolve such issues during the mining process, a mechanical model for describing the deflection of a compound roof was established based on the beam theory for an elastic foundation. The maximum deflection position of a compound roof and the associated depth of the rib spalling were further calculated and determined in this study. Based on the depth of the rib spalling, we determined the force distribution of spalling coal from the mine wall. By combining the force distribution with the safety margin, we established a critical failure equation of the coal wall and further calculated the height of the spalling coal. The human factors used to control the rib spalling issue were also analyzed based on these results. Furthermore, taking the mining conditions of the Pingdingshan No. 11 coal mine as the engineering background, we simulated the mining process on the working face (Ji16-17 -24030) using FLAC 3D numerical modeling software and an orthogonal array testing strategy. By conducting a range analysis on the simulation results, we determined the sensitivity of each main controllable factor to a roof fall and rib spalling in the working face. The results show that the comprehensive sensitivities of the main controllable factors to roof fall and rib spalling follow the order of cohesion > support strength > mining height > distance to face > lateral force. In addition, the maximum deformation of the coal wall decreases by 0.682 mm with every 1 MPa increase in the cohesion strength of the coal body.